Benzotrithiophene versus Benzo/Naphthodithiophene Building Blocks: The Effect of Star‐Shaped versus Linear Conjugation on Their Electronic Structures. Issue 18 (21st March 2016) - Riaño, Alberto; Arrechea‐Marcos, Iratxe; Mancheño, María J.; Mayorga Burrezo, Paula; de la Peña, Alejandro; Loser, Stephen; Timalsina, Amod; Facchetti, Antonio; Marks, Tobin J.; Casado, Juan; López Navarrete, J. Teodomiro; Ponce Ortiz, Rocío; et al.
Abstract: The synthesis, characterization, and optical properties of a novel star‐shaped oligothiophene with a central rigid trithienobenzene (BTT) core and diketopyrrolopyrrole (DPP) units are reported and compared with homologous linear systems based on the benzodithiophene (BDT) and the naphthodithiophene (NDT) units end capped with DPPs. This comparison is aimed at elucidating the effect of the star‐shaped configuration versus linear conformation on the optical and electrical properties. Electronic and vibrational spectroscopies, together with transient absorption spectroscopy, scanning electronic microscopy, and DFT calculations are used to understand not only the molecular properties of these semiconductors, but also to analyze the supramolecular aggregation in these derivatives. We conclude that although the subject star‐shaped derivative is not optimal in terms of π‐conjugation, its extended BTT unit significantly favors intermolecular π‐stacking interactions, which is interesting for their applications in devices. Field‐effect transistors and solar cells were fabricated with these new molecular semiconductors and the performance difference discussed. Abstract : Star‐shaped oligothiophene : The synthesis, characterization, optical, electrical, and photovoltaic properties of a new star‐shaped oligothiophene, BTT‐3 DPP‐6 T, are reported and the data compared with two homologous linear systems, based on the benzodithiophene (BDT) unit, BDT(TDPP)2, and the naphthodithiophene (NDT) unit, NDT(TDPP)2 (see figure).